A Comprehensive Application of Rational Choice Theory: How Costs Imposed by, and Benefits Derived from, the U.S. Federal Government Affect Incidents Perpetrated by the Radical Eco-Movement - Carson, Jennifer Varriale (Journal of quantitative criminology, 2020)
In this study, we examine the effect of both the costs and benefits of perpetration, along with the rewards of abstention, on the behavior of a uniquely rational, yet frequent perpetrator of ideologically-motivated crime: the radical eco-movement.